Analisis Pengaruh Suhu Terhadap Nilai Tegangan Tembus pada Minyak Kacang Tanah Sebagai Isolasi Cair - Setiawan, Aditya Rizky; Dhofir, Moch.; Nurwati, Tri (Jurnal Mahasiswa TEUB, 2024)
This journal discusses the effect of temperature on the breakdown voltage value of peanut oil to determine the suitability of peanut oil as a liquid insulation in high voltage equipment. The temperature increase is done by heating the oil to a predetermined temperature, namely 24.5 ° C (room temperature), 40 ° C, 50 ° C, 60 ° C, and 70 ° C. Electrical testing (a series of breakdown voltage tests), physical (by testing water content using the gravimetric method carried out at the Chemical Engineering Laboratory, Brawijaya University), and calculating the conductivity value (by measuring leakage current using a DC circuit) and permittivity (using an LCR multimeter). The test was carried out to determine the suitability of peanut oil as an insulating oil. The test results showed that the breakdown voltage values of peanut oil at temperatures of 24.5°C (room), 40°C, 50°C, 60°C, and 70°C were respectively 18.36 kV, 19.06 kV, 23.2 kV, 28.18 kV, and 33.95 kV. In the water content test, the values of peanut oil at 24.5°C (room) and peanut oil at 70°C were 993.6 ppm and 486.6 ppm, respectively. In the conductivity test, the values of peanut oil at 24.5°C (room) and peanut oil at 70°C were 21.23× 10^(-9) S/m and 18.22× 10^(-9) S/m, respectively. The results of the relative permittivity test obtained the values of peanut oil at 24.5°C (room temperature) and peanut oil at 70°C were 2.49 and 2.89, respectively. It can be concluded that the effect of increasing temperature can increase the breakdown voltage value of peanut oil, however, from the test data that meets the SPLN 49 standard in 1982, which is 30kV/2.5mm, peanut oil at a temperature of 70°C with a voltage value of 33.95 kV/2.5mm, while at other temperatures it has not met the SPLN 49 standard in 1982. When viewed from the water content level, peanut oil has not met the maximum standard permitted by SPLN 49 in 1982, which is 30 ppm. Keywoards: Breakdown voltage, water content, conductivity, relative permittivity, insulating oil, peanut oi